Synergistic-development of economy, resources, and environment in Guangdong-Hong Kong-Macao Greater Bay Area and its obstacles: a new sustainable framework - Yu, Chengxue; Zheng, Hongbo; Guo, Guangzhen (Frontiers in Environmental Science, 2024)
In recent years, the swift expansion of urban agglomerations has given rise to a profusion of resource and environmental challenges, intensifying the prominent conflict between the imperatives of sustainable development and economic pursuits. This paper clarifies the intricate connection and synergistic dynamics among the economy, resources, and the environment, with the aim of determining their collective influence on the sustainable trajectory of urban agglomerations. Focusing on the exemplary case of Guangdong-Hong Kong-Macao Greater Bay Area, this paper utilizes panel data ranging from 2006 to 2020 to disentangle the spatial-temporal subtleties and obstacles hindering the harmonious development of its economy-resource-environment trinity. Firstly, it integrates the coupling coordination mechanism within the DPSR (Driving Force, Pressure, States, and Response) analytical framework to create a novel sustainable development paradigm. Secondly, it builds a comprehensive evaluation index system to measure the spatial-temporal evolution of the economic-resource-environmental matrix within Greater Bay Area. And thirdly, by employing an obstacle degree model, this paper identifies key obstacles that impede the coordinated progress of the economic-resource-environmental nexus in Greater Bay Area. Lastly, it highlights a continuous upward trajectory in the spatial-temporal evolution of Greater Bay Area, marked by decreasing variations in coupling degrees and enhanced inter-connectivity among the constituent elements. This paper not only provides insights into the complex dynamics shaping urban agglomerations, but also offers actionable intelligence to navigate the multifaceted challenges associated with sustainable development endeavors.